Pelatihan pembuatan minuman kekinian boba herbal untuk immune booster pada remaja di masa pandemi Covid-19 - Nina Hidayatunnikmah; Indria Nuraini; Anik Latifah; Nyna Puspita Ningrum (INDRA: Jurnal Pengabdian kepada Masyarakat, 2022)
An efficient immune response to SARS-Co V-2 may be considered a major solution in Covid-19 cases. Covid-19 can infect all ages including adolescence. The role of parents is important in providing protection to the transmission of Covid-19 infection. Phytochemical herbal ingredients have biological properties as immune system stimulants. Product innovation with herbal ingredients that can attract the attention of adolescence needs to be developed, because it can provide immune booster to them. Therefore, it takes training to improve the skill of parents in making interesting product innovations for adolescence, namely “Bobalthy (Boba Herbal and Healthy)”. The goal was improve the health of adolescents, by making innovations in immune booster products and as business innovations that can be applied during the Covid-19 pandemic. The target of this community service activity were PKK and adolescent parents. The methods were presentation, demonstrations on how to make products “Bobalthy (Boba Herbal and Healthy)”. Evaluation with redemonstration and questionnaires. Outcome this community service activities were increased understanding about herbal ingredients as immune system enhancers and soft skills in the manufacture of innovation products herbal boba that are favored by all adolescents and can simultaneously benefit improving the immune system of adolescents.